2022
DOI: 10.3389/fnut.2022.860693
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Geriatric Nutritional Risk Index With Femur Bone Mineral Density and Osteoporosis in American Postmenopausal Women: Data From the National Health and Nutrition Examination Survey

Abstract: BackgroundThe geriatric nutritional risk index (GNRI) has been used as a significant tool to access the nutritional status of the elderly. However, the relationship between the GNRI and femur bone mineral density (BMD) and the risk of osteoporosis remains unclear in American postmenopausal women.ObjectivesWe aimed to explore associations between the GNRI with femur BMD and the risk of osteoporosis in American postmenopausal women.MethodsWe merged the continuous National Health and Nutrition Examination Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Malnutrition can result in bone metabolism disorders and affect bone remodeling [22]. For people with low AC, it is necessary to restore normal weight to improve the low peak bone mass and accelerate bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can result in bone metabolism disorders and affect bone remodeling [22]. For people with low AC, it is necessary to restore normal weight to improve the low peak bone mass and accelerate bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the relationship between hemoglobin levels and osteoporosis in elderly patients with diabetes found that patients with osteoporosis had lower hemoglobin levels than non-osteoporotic patients, and that higher hemoglobin levels protected against osteoporosis 22 . Researchers investigated the relationship between GNRI and femoral BMD and osteoporosis in postmenopausal women in the USA and found that GNRI, as an indicator of nutritional status, was positively correlated with femoral BMD and negatively correlated with osteoporosis risk 23 . Xiu et al 24 found that serum prealbumin levels were signi cantly associated with osteoporosis and that lower serum prealbumin concentrations increased the risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Building upon prior knowledge regarding the connections between specific nutrients and DOBS, we collectively evaluated 16 nutrients, comprising 2 pro-oxidants and 14 anti-oxidants. 20 The 16 nutrients were classified into tertiles, with anti-oxidant nutrients receiving scores ranging from 0 to 2, and pro-oxidant nutrients receiving scores in reverse order. The detailed scoring strategy for DOBS ingredients is presented in Table S1.…”
Section: Dietary Assessment and Dietary Oxidative Balance Scorementioning
confidence: 99%